A dynamic framework for sustainable open innovation in the food industry. Issue 6 (8th March 2022) - Venturelli, Andrea; Caputo, Andrea; Pizzi, Simone; Valenza, Giuseppe
Abstract : Purpose: This study aims to take a holistic perspective to investigate how open innovation supports sustainability and the contribution to the Unite Nations (UN) Sustainable Development Goals (SDGs). Design/methodology/approach: The study is based on an in-depth single case study of Andriani SpA, a leading Italian company in the food industry. The case is built by triangulating data from direct observations, documentary analysis and semi-structured interviews. Findings: The findings show an organization that has developed its competitive advantage by adopting open innovation to embed sustainability in its strategy and business model. The case study complements the understanding of how open innovation can effectively drive strategic renewal and innovation activities to address sustainability objectives in the food industry. Originality/value: This study contributes to theoretical development by offering new and insightful explanations of firms' strategic behaviour and coevolution toward sustainability via open innovation. It provides practitioners, policymakers, researchers and students with reflections and inspiration about how open innovation may be deployed to support a holistic strategic renewal aimed at sustainability objectives, such as the SDGs, in the food industry.